Bioplastics from orange processing waste and poly(lactic acid) - Laís T. Possari; Marina S. de Paula; George F. Nunes; Iago A. Reis; Marcos V. Basaglia; Caio G. Otoni; Sílvia H.P. Bettini (Future Foods)
Bioplastics have the potential to mitigate the aggravating crisis of plastic pollution. Valorizing agri-food side streams for such a purpose is particularly beneficial as it valorizes massively produced waste, thus contributing to the shift towards circular and regenerative productive chains. In this work, citrus pulp (CP) obtained as a by-product from orange juice production was upcycled into thermoplastic compounds via extrusion-assisted plasticization with glycerol. Compounds with poly(lactic acid) (PLA) were then produced by extrusion melt blending. An experimental 2² factorial design with a central point was performed to evaluate their mechanical, thermal, and biodegradation behavior. The levels for the variables plasticized CP (PCP) and glycerol contents were 30 and 70 % for PCP, and 40 and 60 % for glycerol. Calorimetry showed that PCP increased PLA free volume and chain mobility. Still, the different fractions of PCP and glycerol did not alter the melting behavior of the compounds significantly. PCP led to a progressive toughening effect on PLA. Mass loss after 90 d of soil burial reached 53–64 % for the formulations containing 70 % PCP, and PLA chain scission was accelerated at 30 % PCP with 60 % glycerol, and 70 % PCP with 40 % glycerol. This work opens new pathways to citrus biomass valorization by exploring CP, a scarcely investigated residue, and a novel processing strategy. The produced compounds can be applied as bio-based semi-rigid packaging and utensils.